Investigating the Microbial Dynamics of Hermetia illucens Powder Throughout Rearing and Processing: An Integrated Approach Using Cultural and Metabarcoding Methods - Boris Misery; Lenaïg Brulé; Rima Djema; Xin Yan; Victoire Le Cozic; Guillaume Baudouin; Michel Federighi; Géraldine Boué (Foods, 2025)
The increasing demand for sustainable protein sources highlights Hermetia illucens (Black Soldier Fly, BSF) as a promising alternative. However, microbiological safety remains a key concern. This study investigated the microbial diversity of BSF larvae, comparing two processing methods: (1) boiling followed by drying and (2) drying alone. Microbial diversity was assessed via 16S rRNA sequencing, while bacterial loads were quantified using culture-based methods on samples from a French company. A systematic review complemented this analysis by synthesizing the existing knowledge on BSF microbiota. The rearing conditions varied, with substrate pH ranging from 4.1 to 9.0 and ambient temperatures between 24.6 °C and 42.7 °C. Mesophilic bacteria, spores, and lactic acid bacteria reached up to 8.6, 7.7, and 8.5 log CFU/g in the substrates and larvae, while yeasts, molds, and sulfite-reducing bacteria remained below 4.8 log CFU/g. Boiling reduced most loads below detection thresholds, particularly for yeasts, molds, and ASR. Salmonella, Listeria monocytogenes, Cronobacter sp., and coagulase-positive staphylococci were absent, whereas Clostridium perfringens and Escherichia coli were variably detected. Metabarcoding showed shifts in composition, with Proteobacteria, Bacteroidota, Actinobacteriota, and Firmicutes (Bacillota and Clostridiota) dominating. Process 1 more effectively reduced the bacterial loads, though Bacillus and Clostridium remained. Campylobacter sp. detection in powders raises food safety concerns.